2008
DOI: 10.1155/2008/391259
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Microsynteny ofNPR1with Genes Encoding a Signal Calmodulin-Binding Protein and a CK1-Class Protein Kinase inBeta vulgarisand Two Other Eudicots

Abstract: NPR1 is a gene of central importance in enabling plants to resist microbial attack. Therefore, knowledge of nearby genes is important for genome analysis and possibly for improving disease resistance. In this study, systematic DNA sequence analysis, gene annotation, and protein BLASTs were performed to determine genes near the NPR1 gene in Beta vulgaris L., Medicago truncatula Gaertn, and Populus trichocarpa Torr. & Gray, and to access predicted function. Microsynteny was discovered for NPR1 with genes CaMP, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Coe1 , a DNA transposon within apparent LTRs and other retrotransposon-like features, was discovered on a sugarbeet genomic BAC carrying the NPR1 disease resistance-priming gene [ 7 9 ]. This recent discovery in Beta vulgaris of a unique 16.3 Kb CACTA En/Spm -like transposon named Coe1 [ 7 ] was followed by the finding of conserved microsynteny of NPR1 with another core plant gene whose predicted product has high similarity to a DNA-binding HSF protein [ 8 ]. About 70 Kb of repetitive DNA separates the HSF gene and NPR1 from another small core gene cluster with a CaMP gene specifying a signal peptide calmodulin-binding protein and a gene encoding a CK1-class protein kinase gene [ 8 ], greatly extending and disambiguating the results of the initial sequencing and partial in silico analysis of an NPR1 gene-carrying sugarbeet BAC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coe1 , a DNA transposon within apparent LTRs and other retrotransposon-like features, was discovered on a sugarbeet genomic BAC carrying the NPR1 disease resistance-priming gene [ 7 9 ]. This recent discovery in Beta vulgaris of a unique 16.3 Kb CACTA En/Spm -like transposon named Coe1 [ 7 ] was followed by the finding of conserved microsynteny of NPR1 with another core plant gene whose predicted product has high similarity to a DNA-binding HSF protein [ 8 ]. About 70 Kb of repetitive DNA separates the HSF gene and NPR1 from another small core gene cluster with a CaMP gene specifying a signal peptide calmodulin-binding protein and a gene encoding a CK1-class protein kinase gene [ 8 ], greatly extending and disambiguating the results of the initial sequencing and partial in silico analysis of an NPR1 gene-carrying sugarbeet BAC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This recent discovery in Beta vulgaris of a unique 16.3 Kb CACTA En/Spm -like transposon named Coe1 [ 7 ] was followed by the finding of conserved microsynteny of NPR1 with another core plant gene whose predicted product has high similarity to a DNA-binding HSF protein [ 8 ]. About 70 Kb of repetitive DNA separates the HSF gene and NPR1 from another small core gene cluster with a CaMP gene specifying a signal peptide calmodulin-binding protein and a gene encoding a CK1-class protein kinase gene [ 8 ], greatly extending and disambiguating the results of the initial sequencing and partial in silico analysis of an NPR1 gene-carrying sugarbeet BAC [ 9 ]. In summary, our laboratory has identified, sequenced, and annotated a bacterial artificial chromosome (BAC) carrying the NPR1 disease resistance priming gene of sugarbeet, Beta vulgaris L. [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…parts of leaves base were grown on 5 % and 7 % (PEG 600) media, Showed hyper hydration signs, that is look like callous appearance. Researchers stated that water deficiency stress is a crucial factor for the initial phase of plant growth and development, which affects plant growth and elongation (Kusaka et al, 2005;Kuykendall et al, 2008;Jaleel et al, 2009;Anjum et al, 2011). Moreover, Moosavi et al (2017) reported that drought effects on dry weight of leaf, root, crown, total dry weight and root crop, Also drought stress effect on leaf temperature characters of different genotypes of sugar beet.…”
Section: -Morphological Changesmentioning
confidence: 99%
“…Also, an HSF gene adjacent to, just 2 Kb downstream from, NPR1 in sugarbeet and whose close microsynteny is conserved in four out of five eudicots examined, encodes a DNA-binding HSF protein similar to that specified by gene HSFA9 that controls early leaf morphogenesis in sunflower [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, complete BAC sequence analysis identified two core plant genes, CaMP and CKI , tightly physically linked to the disease resistance controlling gene NPR1 and established a conservation of microsynteny between the NPR1 gene regions of sugarbeet and other eudicots [ 4 ]. Also, an HSF gene adjacent to, just 2 Kb downstream from, NPR1 in sugarbeet and whose close microsynteny is conserved in four out of five eudicots examined, encodes a DNA-binding HSF protein similar to that specified by gene HSFA9 that controls early leaf morphogenesis in sunflower [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%